Preparation method and application of alkali metal ion doped sodium vanadyl fluorophosphate carbon composite material

By doping lithium or potassium on the Na site and compounding it with nitrogen-carbon composite material, the electronic conductivity and cyclic stability of the NVOPF positive electrode material are improved, and the problems of low conductivity and poor stability of existing materials are solved, so as to achieve A positive electrode material of a water-based zinc ion battery with high magnification and long cycle stability.

CN119400830AActive Publication Date: 2025-02-07GUANGDONG UNIV OF TECH
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411545809.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-07
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

The existing NVOPF cathode material has problems such as low conductivity, poor stability, complex process, high cost and unfavorable large-scale development in aqueous zinc ion batteries, which is difficult to meet the needs of high magnification and long cycle stability.

Method used

Microwave hydrothermal assisted calcination method doped with lithium or potassium metal elements on the Na site and composited with high electron conductivity nitrogen-carbon composite material to prepare N2.85L0.15VOPF@NC or N2.85K0.15VOPF@ NC material.

Benefits of technology

It improves the electronic conductivity of the material, enhances the rate performance and cycle stability, reduces production costs and process complexity, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119400830A_ABST
    Figure CN119400830A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electrode materials, and particularly relates to a preparation method and application of an alkali metal ion doped sodium vanadyl fluorophosphate carbon composite material. According to the invention, three methods of surface carbon coating modification, morphology modification and metal ion doping modification are combined, and the prepared lithium-doped sodium vanadyl fluorophosphate or potassium-doped sodium vanadyl fluorophosphate is used as an aqueous zinc ion battery positive electrode material, so that the battery can obtain excellent rate capability and stable cycle performance; and meanwhile, the structural stability of the battery in the long-cycle process can be ensured. The microwave hydrothermal assisted calcination method which is rapid in reaction, low in cost and capable of achieving a large scale is adopted, the reaction time can be greatly shortened, and the production efficiency can be improved. Meanwhile, the NVOPF is compounded with a nitrogen-carbon material with high electronic conductivity, and metal elements are doped at sodium element sites, so that the nitrogen-carbon compounded aqueous zinc ion battery positive electrode material with high magnification and long cycle stability can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrode materials, and in particular relates to a preparation method and application of an alkali metal ion-doped sodium vanadium fluorophosphate@carbon composite material. Background Art

[0002] With the development of large-scale energy storage equipment, the demand and requirements for batteries are increasing. Among them, lithium-ion batteries are widely used in 3C consumer electronics, electric vehicles, and military industries due to their advantages such as high energy density, long service life, low self-discharge rate, and mature preparation process. However, the shortcomings of lithium ions have also been gradually exposed, such as the uneven distribution of lithium resources leading to rising prices, the easy generation of lithium dendrites under overcharging causing battery short circuits, and the use of organic electrolytes with toxicity, low ignition point, and poor thermal stability. These problems seriously limit the further application of lithium-ion batteries in the field of large-scale energy storage. Therefore, it is of great significance for the development of human civilization to develop a low-cost, safe, and environmentally friendly secondary battery as a candidate for large-scale energy storage power stations to cope with the existing energy crisis.

[0003] Aqueous zinc-ion batteries (AZIBs) are widely favored due to their low cost, high safety and environmental friendliness. Therefore, the successful development and application of AZIBs in the field of safe and efficient large-scale energy storage has become a common goal. The negative electrode of aqueous zinc-ion batteries usually uses metallic zinc, which is due to the good chemical stability and reversibility of metallic zinc in aqueous electrolytes. At the same time, metallic zinc as the negative electrode can provide a high mass specific capacity (820mAh g -1 ) and volumetric capacity (5855 mAh cm -3 ). And the aqueous electrolyte has a higher conductivity than the organic electrolyte (1~10mS·cm -1 ) Higher ionic conductivity, about 1S·cm -1 , high conductivity can ensure that the migration dynamics of zinc ions can meet the requirements of higher rate charge and discharge, and the aqueous electrolyte has natural flame retardant properties, which can meet high safety indicators. In addition, aqueous zinc-ion batteries can be assembled directly under air, greatly reducing manufacturing and use costs. Therefore, aqueous zinc-ion batteries are considered to be one of the competitive candidates for the next generation of large-scale energy storage power stations.

[0004] At present, since AZIBs are still in the early stages of development, finding suitable zinc storage materials is the key, and positive electrode materials with zinc storage activity are the top priority. However, there are still the following problems in positive electrode materials: (1) Zn 2+Large electrostatic interactions can easily lead to large internal stresses during repeated insertion / extraction of the material structure, causing the crystal structure to collapse or even surface cracking, resulting in the inactivation of effective zinc storage sites and reduced capacity and cycle stability; (2) Low electronic conductivity leads to low capacity at high rates; (3) It is easy to induce transition metal dissolution in aqueous electrolytes. Therefore, researching and developing a positive electrode material system that can cope with the above problems is a key step at present. At present, the positive electrode materials with zinc storage activity reported at home and abroad mainly include manganese-based positive electrodes, vanadium-based positive electrodes, Prussian blue analogs and organic materials. Among them, vanadium-based phosphates (M3V2(PO4)3, M=Li, Na, K) have a higher average voltage (>1.15V) due to the presence of [PO4] polyanion groups, and their crystal structure is an open skeleton composed of oxygen atoms on the shared corners of [PO4] tetrahedrons and [VO6] octahedrons, so Na + / Zn 2+ There is enough migration space in the channel, so it is also called fast sodium ion conductor structure (NASICON), and the PO bond has high binding energy, which can ensure the structural stability of the material. The above advantages have attracted the attention of a large number of researchers. At the same time, due to its suitable Zn 2+ Compared with Prussian blue analogs, vanadium-based phosphates have higher theoretical capacity, better cycle life and higher rate capacity; compared with manganese-based positive electrode materials, vanadium-based phosphates have a more stable structure, mainly because of the large diffusion channels, good structural stability and high voltage. 2+ / H + Repeated embedding and extraction of the lattice, the formation and disappearance of by-products can easily cause structural damage to MnO2, which in turn causes the material to fall off, ultimately leading to poor cycle stability and significant capacity decay. In addition, vanadium-based phosphates are more suitable for aqueous batteries, while Mn dissolves more severely in water, which will further cause a reduction in active materials and reduce battery capacity. However, the low electronic conductivity of the NASICON material affects its rate performance, and vanadium dissolution will also reduce cycle stability.

[0005] NVOPF(Na2V6O 16·3H2O), also known as hydrovanadium sodium, is a layered vanadium oxide with adjustable crystal structure and high capacity. It is one of the cathode materials widely studied at this stage. Its stability and cycle life at high rates make it a promising cathode material, which is expected to promote the application and development of aqueous zinc-ion batteries in the field of energy storage. At present, in the research on the application of sodium vanadium oxyfluorophosphate (NVOPF) in the cathode materials of aqueous zinc-ion batteries, most of its preparation methods are relatively complicated, time-consuming and costly, and even cause pollution to the environment, and cannot meet the requirements of large-scale energy storage. For example, NVOPF is currently generally prepared by one-step hydrothermal synthesis or high-temperature calcination after synthesizing the precursor. However, the hydrothermal reaction synthesis cycle is long and the operation steps are relatively complicated. The synthesis of the precursor usually adopts ball milling, hydrothermal / solvothermal method, electrospinning method, spray drying method, etc. Among them, the advantages of the ball milling method are that it can significantly reduce the reaction activation energy, improve the electrochemical properties of the material, simple process, and can be mass-produced, but its disadvantages are long ball milling time and high noise. The advantage of the hydrothermal method is that it can create a high temperature and high pressure environment in a sealed container, but the disadvantage is that the reaction time is relatively long. The advantages of electrospinning are simple manufacturing equipment, low spinning cost, and controllable process. The disadvantage is the presence of toxic solvents in the polymer solution, which not only pollutes the environment and is not conducive to recycling, but also has a low fiber yield. The advantage of the spray drying method is that the drying process is very rapid and the production efficiency is high. The disadvantages are that the equipment is relatively complex, occupies a large area, the one-time investment is too large, the powder recovery device is relatively expensive, the thermal efficiency is not high, and the heat consumption is large. At the same time, although the NVOPF material has good foresight as a high-performance AZIBs positive electrode, its structure itself has Vt 2g The non-bonding orbitals result in a large band gap (~2 eV) and low electronic conductivity (~10 -7 S cm -1 ), and there is also a dissolution problem in aqueous electrolytes, so the NVOPF material needs to be further modified to improve its zinc storage performance and stability.

[0006] At present, the modification methods of NVOPF positive electrode materials mainly include surface carbon coating modification, morphology modification and metal ion doping modification. Among them, surface carbon coating modification is to coat a layer of chemically stable and conductive material on the surface, which is beneficial to improve the transmission path of electrons and ions between material particles, improve the conductivity of the material, and provide a stable chemical and electrochemical reaction interface. Morphology modification is mainly to increase the specific surface area and active sites of the material by reducing the particle size and synthesizing spherical, rod-shaped, sheet-shaped, spindle-shaped, micro-nano spherical and other morphologies, shortening the Na +Transmission distance, thereby improving the conductivity and rate performance of the material. Metal ion doping modification is to dope certain metal ions with good conductivity into the lattice of the material. This method can produce lattice defects or electron holes in the material without changing the crystal structure, thereby effectively and directly improving the intrinsic electronic and ionic conductivity of the material. At present, the surface carbon coating modification method is mainly to coat redox graphene, graphene and amorphous carbon. The morphology modification is mainly nano-sheet flower and micron ball modification. The method of metal ion doping modification is mainly to dope metal elements at the vanadium element site, such as Mg 2+ and Mn + However, the NVOPF cathode materials obtained by these current modification methods still have the disadvantages of low conductivity, poor stability, complex process, high cost, and disadvantageous for large-scale production, and it is urgent to develop better optimization and improvement strategies. Summary of the invention

[0007] In order to overcome the above-mentioned shortcomings of the prior art, the present invention uses a microwave hydrothermal assisted calcination method that is fast, low-cost and scalable to obtain lithium-doped sodium vanadium fluorophosphate (N 2.85 L 0.15 VOPF@NC) or potassium-doped sodium vanadyl fluorophosphate (N 2.85 K 0.15 VOPF@NC), thereby solving the problem of aqueous electrolyte dissolving the positive electrode while ensuring the integrity of the electrode material and improving the electronic conductivity of the material.

[0008] In order to achieve the above object, the technical solution adopted by the present invention is:

[0009] The first aspect of the present invention provides a method for preparing an alkali metal ion-doped sodium vanadium oxyfluorophosphate@carbon composite material, the method comprising the following steps:

[0010] S1, dissolving vanadium acetylacetonate in ethanol, and separately dissolving sodium fluoride, ammonium dihydrogen phosphate and potassium fluoride or lithium fluoride in water, combining the two solutions and subjecting them to microwave hydrothermal reaction, and washing and drying after the reaction to obtain a precursor;

[0011] S2, dissolving the precursor of step S1, dopamine hydrochloride, trishydroxymethylaminomethane and polyether P123 in water, drying and calcining in an inert gas atmosphere to obtain N 2.85 L 0.15 VOPF@NC or N 2.85 K 0.15 VOPF@NC.

[0012] The microwave hydrothermal method used in the present invention can effectively solve the problems of long production time, high noise, low output and low heat conversion efficiency. The advantages of the microwave hydrothermal method are mild conditions, low energy consumption, fast reaction speed, small product particle size, uniform distribution, light particle agglomeration, good and controllable crystal shape. At the same time, NVOPF is compounded with a carbon material with high electronic conductivity and doped with metal elements to further improve the electronic conductivity of the material.

[0013] Preferably, the temperature of the microwave hydrothermal reaction in S1 is 120-140°C, the heating rate is 7-13°C / min, and the time is 1-3h.

[0014] Preferably, the molar ratio of vanadium acetylacetonate, sodium fluoride, ammonium dihydrogen phosphate and potassium fluoride or lithium fluoride in S1 is 0.6-0.8: 0.9-1.1: 0.1-0.2: 1.0-1.2.

[0015] Preferably, the mass ratio of the precursor in S2 to dopamine hydrochloride, trishydroxymethylaminomethane and polyether P123 is 100:40:40:16.

[0016] Preferably, the calcination temperature in S2 is 500-700°C and the calcination time is 6-8h.

[0017] Preferably, the washing in S1 is to wash the reaction solution with water and ethanol respectively, and then collect the precipitate by high-speed centrifugation 3-7 times.

[0018] More preferably, the rotation speed of the high-speed centrifugation is not less than 6000 r / min.

[0019] The second aspect of the present invention provides an alkali metal ion-doped sodium vanadium oxyfluorophosphate@carbon composite material prepared by the preparation method described in the first aspect.

[0020] The present invention combines three methods: surface carbon coating modification, morphology modification and metal ion doping modification. Among them, a microwave hydrothermal method is used to form NVOPF with small particle size and uniform distribution; a carbon composite material is coated on the surface of NVOPF to improve the conductivity between particles and stabilize its morphology; and a method of sodium element site doping by alkali metal ions can improve the intrinsic electronic and ionic conductivity of the NVOPF material. Therefore, the NVOPF prepared by the method of the present invention is 2.85 L 0.15 VOPF@NC or N 2.85 K 0.15 As a positive electrode material for aqueous zinc-ion batteries, VOPF@NC can enable the battery to achieve excellent rate performance and stable cycle performance, while ensuring the structural stability of the battery during long cycles.

[0021] The third aspect of the present invention provides the use of the alkali metal ion-doped sodium vanadium fluorophosphate@carbon composite material described in the second aspect in the preparation of a positive electrode material for an aqueous zinc ion battery.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The invention adopts acetylacetonato vanadyl as a vanadium source, sodium fluoride as a sodium source and a fluorine source, ammonium dihydrogen phosphate as a phosphate source, and potassium fluoride or lithium fluoride as a doping source. After the raw materials are mixed, they are rapidly reacted in a microwave hydrothermal manner to obtain a precursor, and then the precursor, dopamine hydrochloride, trishydroxymethylaminomethane and polyether P123 are dissolved in water, and after drying, high-temperature calcination is performed under the condition of passing inert gas to obtain lithium-doped sodium vanadyl fluorophosphate (N 2.85 L 0.15 VOPF@NC) or potassium-doped sodium vanadyl fluorophosphate (N 2.85 K 0.15 VOPF@NC), and its XRD data were refined by fullprof. It was found that K ions and Na ions doped at the Na position could obtain good refinement factors, indicating that K ions or Li ions were doped at the Na position. 2.85 L 0.15 VOPF@NC or N 2.85 K 0.15 As a positive electrode material for aqueous zinc-ion batteries, VOPF@NC can enable the battery to achieve excellent rate performance and stable cycle performance, while ensuring the structural stability of the battery during long cycles.

[0024] The present invention adopts a microwave hydrothermal assisted calcination method that is fast in reaction, low in cost and can be scalable, which can greatly shorten the reaction time and help improve production efficiency. At the same time, the NVOPF is compounded with a nitrogen-carbon material with high electronic conductivity, and a method of doping a metal element at the sodium element site improves the electronic conductivity of the material from both the material body and the material surface, thereby obtaining a high-rate, long-cycle stable nitrogen-carbon composite aqueous zinc ion battery positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 N 2.85 L 0.15 X-ray diffraction spectrum of VOPF@NC (above) and schematic spectrum refined by fullprof (below);

[0026] Figure 2 N 2.85 L 0.15 Scanning electron microscope image of VOPF@NC;

[0027] Figure 3 N2.85 L 0.15 Rate performance diagram of VOPF@NC as a cathode material for aqueous zinc-ion batteries at current densities of 0.5-30C;

[0028] Figure 4 N 2.85 L 0.15 Cycling performance of VOPF@NC as a cathode material for aqueous zinc-ion batteries at a current density of 30C after activation for 5 cycles at a current density of 0.5-30C;

[0029] Figure 5 N 2.85 L 0.15 Scanning electron microscopy image of VOPF@NC as a cathode material for aqueous zinc-ion batteries after 50 cycles at a current density of 0.5-30C;

[0030] Figure 6 N 2.85 K 0.15 X-ray diffraction spectrum of VOPF@NC (above) and schematic spectrum refined by fullprof (below);

[0031] Figure 7 N 2.85 K 0.15 Scanning electron microscope image of VOPF@NC;

[0032] Figure 8 N 2.85 K 0.15 Rate performance diagram of VOPF@NC as a cathode material for aqueous zinc-ion batteries at current densities of 1-30C;

[0033] Fig. 9 N 2.85 K 0.15 Cycling performance of VOPF@NC as a cathode material for aqueous zinc-ion batteries at a current density of 20C after activation for 10 cycles at a current density of 1C;

[0034] Fig.10 N 2.85 K 0.15 Scanning electron microscopy image of VOPF@NC as a cathode material for aqueous zinc-ion batteries after 50 cycles at a current density of 1C;

[0035] Fig.11 is the X-ray diffraction spectrum of NVOPF;

[0036] Fig.12 is the scanning electron microscope image of NVOPF;

[0037] Fig.13This is the rate performance diagram of NVOPF as a positive electrode material for aqueous zinc-ion batteries at a current density of 1-30C;

[0038] Fig.14 This is the cycle performance diagram of NVOPF as the positive electrode material of aqueous zinc-ion battery at a current density of 20C after being activated for 10 cycles at a current density of 1C;

[0039] Fig.15 This is a scanning electron microscope image of NVOPF as a positive electrode material for aqueous zinc-ion batteries after 50 cycles at a current density of 1C. DETAILED DESCRIPTION

[0040] The specific embodiments of the present invention are further described below. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0041] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are commercially available unless otherwise specified.

[0042] Example 1: Lithium-doped sodium vanadium fluorophosphate (N 2.85 Li 0.15 Preparation of VOPF@NC) and its application as cathode material for aqueous zinc-ion batteries

[0043] 1. N 2.85 Li 0.15 Preparation of VOPF@NC:

[0044] 1.019mmol sodium fluoride (NaF), 0.15mmol lithium fluoride (LiF) and 1.05mmol ammonium dihydrogen phosphate (NH4H2PO4) were stirred and dissolved in 12mL of deionized water, and 0.7mmol vanadyl acetylacetonate (C 10 H 14O5V) was stirred and dissolved in 24mL of anhydrous ethanol. After combining the two solutions, continue stirring and add 18mL of deionized water to ensure the pressure of the reactor. The obtained mixed solution was then placed in a polytetrafluoroethylene liner, and the temperature was raised from room temperature to 130°C by microwave-assisted heating, with a heating rate of 10°C / min, and kept at 130°C for 1h. After the reaction, the reaction solution was cleaned with deionized water and anhydrous ethanol by high-speed centrifugation (6000r / min) three times, and the precipitate was collected and placed in a 60°C drying oven for 10h to obtain the precursor after complete drying. Then 100mg of the precursor, 40mg of dopamine hydrochloride, 40mg of trihydroxymethylaminomethane and 16mg of polyether P123 were weighed and added to 100mL of deionized water, stirred for 12h until dissolved, then filtered and dried in a 60°C oven for 12h. Finally, the obtained product was placed in a tubular furnace with argon and calcined at 600°C for 7h to obtain N 2.85 Li 0.15 VOPF@NC.

[0045] like Figure 1 As shown, the N prepared in this embodiment 2.85 Li 0.15 The peak position and peak intensity of the X-ray diffraction spectrum of VOPF@NC correspond to the standard card, with no other impurities and sharp peaks, indicating that the purity and crystallinity of the material are good. At the same time, through the fullprof refinement of its XRD data, it was found that Li ion doping at the Na position can obtain a good refinement factor, indicating that Li ion doping at the Na position. Figure 2 As shown, the N prepared in this embodiment 2.85 Li 0.15 The particle size of VOPF@NC is 40-70nm.

[0046] 2. The N obtained in this embodiment 2.85 Li 0.15 VOPF@NC is used as a cathode material in aqueous zinc-ion batteries. The specific implementation method is as follows:

[0047] The above N 2.85 Li 0.15 VOPF@NC was ground with conductive carbon black and sodium carboxymethyl cellulose (CMC-Na) in a mass ratio of 7:2:1, and a proper amount of deionized water was added to mix to form a uniform and fine slurry. The slurry was then evenly coated on a 12mm diameter round stainless steel mesh and placed in an oven at 60°C for 12 hours. Finally, the stainless steel mesh loaded with active substances was used as the positive electrode and the metal zinc was used as the negative electrode to assemble the button cell, and the charge and discharge test was performed in the voltage window range of 0.4-1.9V.

[0048] Test the N prepared in this embodiment 2.85 Li0.15 VOPF@NC as a positive electrode material for aqueous zinc-ion batteries has rate performance at current densities of 0.5, 1, 2, 5, 10, 20, and 30C. Figure 3 As shown, the battery provided 147.4, 140.4, 128.9, 113.4, 93.4, and 70 mAh g at different current densities. -1 When the current density returns to 0.1A g -1 The charge capacity provided by the test battery is 155 mAh g -1 Compared with the first week, the capacity retention rate is 105%, which reflects the excellent rate performance.

[0049] Test the N prepared in this example 2.85 Li 0.15 Cycling performance of VOPF@NC as a cathode material for aqueous zinc-ion batteries after activation at 0.5C for 5 cycles and then at 30C. Figure 4 As shown in the figure, the first week charging capacity of the battery is 54.1 mAh g -1 After 4000 cycles, the charge capacity provided is 47.2 mAh g -1 , showing stable cycle performance.

[0050] The N prepared in this example 2.85 Li 0.15 SEM scan of VOPF@NC as a positive electrode material for aqueous zinc-ion batteries after 50 cycles at 0.5C. Figure 5 As shown, it can be found that the morphology of the positive electrode material is well maintained, indicating that carbon coating can stabilize the structure of the material and prevent the positive electrode from dissolving.

[0051] Example 2: Potassium-doped sodium vanadium fluorophosphate (N 2.85 K 0.15 Preparation of VOPF@NC) and its application as cathode material for aqueous zinc-ion batteries

[0052] 1. N 2.85 K 0.15 Preparation of VOPF@NC:

[0053] 1.019mmol sodium fluoride (NaF), 0.15mmol lithium fluoride (KF) and 1.05mmol ammonium dihydrogen phosphate (NH4H2PO4) were stirred and dissolved in 12mL of deionized water, and 0.7mmol acetylacetonatovanadium (C 10 H 14O5V) was stirred and dissolved in 24mL of anhydrous ethanol. After combining the two solutions, the stirring was continued and 18mL of deionized water was added to ensure the pressure of the reactor. The obtained mixed solution was then placed in a polytetrafluoroethylene liner, and the temperature was raised from room temperature to 130°C by microwave-assisted heating, with a heating rate of 10°C / min, and kept at 130°C for 1h. After the reaction, the reaction solution was washed with deionized water and anhydrous ethanol respectively, and centrifuged at high speed (6000r / min) three times, and the precipitate was collected and placed in a 60°C drying oven for 10h to obtain the precursor after complete drying. Then 100mg of the precursor, 40mg of dopamine hydrochloride, 40mg of trihydroxymethylaminomethane and 16mg of polyether P123 were weighed and added to 100mL of deionized water, stirred for 12h until dissolved, then filtered and dried in a 60°C oven for 12h. Finally, the obtained product was placed in a tubular furnace with argon and calcined at 600°C for 7h to obtain N 2.85 K 0.15 VOPF@NC.

[0054] like Figure 6 As shown, the N prepared in this embodiment 2.85 K 0.15 The peak position and peak intensity of the X-ray diffraction spectrum of VOPF@NC correspond to the standard card, with no other impurities and sharp peaks, indicating that the purity and crystallinity of the material are good. At the same time, through the fullprof refinement of its XRD data, it was found that K ion doping at the Na position can obtain a good refinement factor, indicating that K ion doping at the Na position. Figure 7 As shown, the N prepared in this embodiment 2.85 K 0.15 The particle size of VOPF@NC is 40-70nm.

[0055] The N obtained in this example 2.85 K 0.15 VOPF@NC is used as a cathode material in aqueous zinc-ion batteries. The specific implementation method is as follows:

[0056] The above N 2.85 K 0.15 VOPF@NC was ground with conductive carbon black and sodium carboxymethyl cellulose (CMC-Na) in a mass ratio of 7:2:1, and a proper amount of deionized water was added to mix to form a uniform and fine slurry. The slurry was then evenly coated on a 12mm diameter round stainless steel mesh and placed in an oven at 60°C for 12 hours. Finally, the stainless steel mesh loaded with active substances was used as the positive electrode and the metal zinc was used as the negative electrode to assemble the button cell, and the charge and discharge test was performed in the voltage window range of 0.4-1.9V.

[0057] Test the N prepared in this embodiment 2.85 K 0.15The rate performance of VOPF@N as a positive electrode material for aqueous zinc-ion batteries at current densities of 1, 2, 5, 10, 20, and 30C. Figure 8 As shown, the battery provided 125, 121.4, 113.7, 99.1, 78.8, and 62.9 mAh g at different current densities. -1 When the current density returns to 0.1A·g -1 The charge capacity provided by the test battery is 134 mAh g -1 Compared with the first week, the capacity retention rate is 107%, which reflects the excellent rate performance.

[0058] Test the N prepared in this example 2.85 K 0.15 Cycling performance of VOPF@NC as a cathode material for aqueous zinc-ion batteries after activation at 1C for 10 cycles and then at 20C. Fig. 9 As shown in the figure, the first week charging capacity of the battery is 66.8 mAh g -1 After 4000 cycles, the charge capacity provided is 53.3 mAh g -1 , showing stable cycle performance.

[0059] The N prepared in this example 2.85 K 0.15 SEM scan of VOPF@NC as a positive electrode material for aqueous zinc-ion batteries after 50 cycles at 1C. Fig.10 As shown, it can be found that the morphology of the positive electrode material is well maintained, indicating that carbon coating can stabilize the structure of the material and prevent the positive electrode from dissolving.

[0060] Comparative Example 1: Preparation of NVOPF and its application as positive electrode material for aqueous zinc ion batteries

[0061] 1. Preparation of NVOPF:

[0062] 1.169mmol sodium fluoride (NaF) and 1.05mmol ammonium dihydrogen phosphate (NH4H2PO4) were stirred and dissolved in 12mL deionized water, and 0.7mmol acetylacetonatovanadium (C 10 H 14O5V) was stirred and dissolved in 24mL of anhydrous ethanol. After the two solutions were combined, stirring was continued and 18mL of deionized water was added to ensure the pressure of the reactor. The obtained mixed solution was then placed in a polytetrafluoroethylene liner, and the temperature was raised from room temperature to 130°C by microwave-assisted heating, with a heating rate of 10°C / min, and kept at 130°C for 1h. After the reaction, the reaction solution was washed with deionized water and anhydrous ethanol respectively, and centrifuged at high speed (6000r / min) three times, and the precipitate was collected and placed in a 60°C drying oven for 10h. After complete drying, the precursor was obtained. Finally, the obtained precursor was placed in a tubular furnace with argon gas and calcined at 600°C for 7h to obtain the product, which was recorded as: NVOPF.

[0063] like Fig.11 As shown in the figure, the peak position and peak intensity of the X-ray diffraction spectrum of the prepared NVOPF correspond to those of the standard card, there are no other impurity peaks and the peak shape is sharp, indicating that the purity and crystallinity of the material are good. Fig.12 As shown, the particle size of the prepared NVOPF is 30-60 nm.

[0064] 2. The obtained NVOPF is used as a positive electrode material in an aqueous zinc ion battery. The specific implementation method is as follows:

[0065] The above-mentioned NVOPF was ground with conductive carbon black and sodium carboxymethyl cellulose (CMC-Na) in a mass ratio of 7:2:1, and an appropriate amount of deionized water was added to mix to form a uniform and fine slurry. The slurry was then evenly coated on a 12mm diameter round stainless steel mesh and placed in an oven at 60°C for 12 hours. Finally, the stainless steel mesh loaded with active substances was used as the positive electrode and the metal zinc was used as the negative electrode to assemble the button cell, and the charge and discharge test was performed within the voltage window of 0.4-1.9V.

[0066] The prepared NVOPF was tested as a positive electrode material for aqueous zinc ion batteries at a current density of 1, 2, 5, 10, 20, and 30C. Fig.13 As shown in the figure, the battery provides 121.4, 75.3, 57.6, 41.3, 30.5, and 28.8 mAh g at different current densities. -1 When the current density returns to 1C, the charge capacity provided by the test battery is 80.6mAh·g -1 Compared with the first week, the capacity retention rate is 66%, and the rate performance is average.

[0067] The prepared NVOPF was tested as a positive electrode material for aqueous zinc-ion batteries after being activated for 10 cycles at 1C and then at 20C. Fig.14 As shown in the figure, the first week charging capacity of the battery is 44.1 mAh g -1, it cannot cycle 4000 times, and its cycle performance is relatively weak.

[0068] The prepared NVOPF was used as the positive electrode material for aqueous zinc-ion batteries and then cycled 50 times at 1C to perform SEM scanning. Fig.15 As shown, it can be found that flaky byproducts have grown on the positive electrode material.

[0069] In summary, the present invention uses a microwave hydrothermal assisted calcination method that is fast, low-cost and scalable to dope lithium or potassium metal elements at the Na site, and composites NVOPF with a nitrogen-carbon composite material with high electronic conductivity to obtain N 2.85 L 0.15 VOPF@NC or N 2.85 K 0.15 VOPF@NC, while ensuring the integrity of the electrode material, solves the problem of aqueous electrolyte dissolving the positive electrode, and improves the electronic conductivity of the material, thereby obtaining a high-rate, long-cycle stable nitrogen-carbon composite aqueous zinc-ion battery positive electrode material.

[0070] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the protection scope of the present invention.

Claims

1. A method for preparing an alkali metal ion-doped sodium vanadium fluorophosphate@carbon composite material, characterized in that: The following steps are involved: S1, dissolving vanadium acetylacetonate in ethanol, and separately dissolving sodium fluoride, ammonium dihydrogen phosphate and potassium fluoride or lithium fluoride in water, combining the two solutions and subjecting them to microwave hydrothermal reaction, and washing and drying after the reaction to obtain a precursor; S2, dissolving the precursor of step S1, dopamine hydrochloride, trishydroxymethylaminomethane and polyether P123 in water, drying and calcining in an inert gas atmosphere to obtain lithium-doped sodium vanadyl fluorophosphate or potassium-doped sodium vanadyl fluorophosphate.

2. The method for preparing an alkali metal ion-doped sodium vanadium fluorophosphate@carbon composite material according to claim 1, characterized in that: S1 The temperature of the microwave hydrothermal reaction is 120-140°C, the heating rate is 7-13°C / min, and the time is 1-3h.

3. The method for preparing an alkali metal ion-doped sodium vanadium fluorophosphate@carbon composite material according to claim 1, characterized in that: S1 The molar ratio of vanadium acetylacetonate, sodium fluoride, ammonium dihydrogen phosphate and potassium fluoride or lithium fluoride is 0.6-0.8: 0.9-1.1: 0.1-0.2: 1.0-1.

2.

4. The method for preparing an alkali metal ion-doped sodium vanadium fluorophosphate@carbon composite material according to claim 1, characterized in that: The mass ratio of the precursor S2 to dopamine hydrochloride, trihydroxymethylaminomethane and polyether P123 is 100:40:40:

16.

5. The method for preparing an alkali metal ion-doped sodium vanadium fluorophosphate@carbon composite material according to claim 1, characterized in that: The calcination temperature in S2 is 500-700°C and the calcination time is 6-8h.

6. The method for preparing an alkali metal ion-doped sodium vanadium fluorophosphate@carbon composite material according to claim 1, characterized in that: The washing in S1 is to wash the reaction solution with water and ethanol respectively, and then collect the precipitate by high-speed centrifugation 3-7 times.

7. The method for preparing an alkali metal ion-doped sodium vanadium fluorophosphate@carbon composite material according to claim 6, characterized in that: The rotation speed of the high-speed centrifuge is not less than 6000r / min.

8. Alkali metal ion-doped sodium vanadium oxyfluorophosphate@carbon composite material prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the alkali metal ion-doped sodium vanadium fluorophosphate@carbon composite material according to claim 8 in the preparation of positive electrode materials for aqueous zinc ion batteries.

Citation Information

Patent Citations

  • Doped and modified sodium vanadium fluorophosphate cathode material and preparation method thereof

    CN107819115A

  • Monocrystal sodium vanadyl fluorophosphate / carbon positive electrode material and preparation method and application thereof

    CN115084473A

  • Porous single-crystal sodium vanadyl fluorophosphate positive electrode material as well as preparation method and application thereof

    CN115084474A

  • Preparation method and application of sodium vanadium oxyfluoride phosphate composite positive electrode material

    CN115583644A

  • Surface-doped and coated sodium ion battery positive electrode material as well as preparation and application thereof

    CN118173732A